Menumbuhkan Kewirausahaan Kreatif: Melalui Ketrampilan Menjahit Menjadi Usaha - Slahanti, Masine; Novia Avien Christy, Nisa; Setiadi, Sofyandanu; Dhian Pratamanti, Enggar (Literasi Jurnal Pengabdian Masyarakat dan Inovasi, 2025)
Creative entrepreneurship is a key factor in improving the economic well-being of the community, particularly among housewives. While mothers possess sewing skills, they have not yet been utilized optimally. Sewing skills have significant potential to be developed into creative businesses with economic value.Through this community service, participants, particularly mothers, will be motivated, equipped with knowledge, and skills to sew a variety of simple yet valuable products, such as tote bags, aprons, and decorative pillows, which can be transformed into entrepreneurial ventures. Furthermore, participants will be equipped with basic strategies for developing creative products and managing a small business, from product planning to simple offline and online marketing.Activities provided to the mothers of RT001 and RT002 from RW010, Kemijen Village, East Semarang, sewing skills can be beneficial and motivated, not just as a regular household activity but also to develop into independent and sustainable creative businesses. This program aims to foster a creative entrepreneurial spirit, increase the competitiveness of local products, and improve the family economy.